The Influence of Sense of Community and Satisfaction With E-Learning and Their Impact on Nursing Students’ Academic Achievement - Innab, Adnan; Albloushi, Monirah; Alruwaili, Mohammed; Alqahtani, Naji; Alenazi, Latifah; Alkathiri, Alwah (International Review of Research in Open and Distributed Learning, 2022)
The COVID-19 pandemic has caused a sudden shift to distance learning. For many nursing students, distance learning is a new experience and an essential requirement if they hope to complete their programs. Two challenges that nursing students could face during e-learning are the lack of social presence and low satisfaction. This study aimed to assess students’ sense of community and satisfaction during e-learning and determine their impacts on academic achievement. This cross-sectional descriptive study used convenience sampling to collect data via a student satisfaction survey and a classroom community scale. There was a positive and significant correlation between the sense of community, total satisfaction with e-learning (p < .001), and academic achievement (p < .001). Academic achievement was positively and strongly correlated with satisfaction with teaching (p < .001), assessment (p < .001), generic skills and learning experiences (p < .001), and total satisfaction with e-learning (p < .001). Students who worked collaboratively with their classmates and were more engaged in their learning were more satisfied with e-learning and had higher academic achievement (p < .01). Female participants reported a strong sense of community and satisfaction with e-learning and greater academic achievement than males. Junior students perceived higher satisfaction scores and greater academic achievement (p < .01) than senior students. The findings of this study suggest that failing to meet student expectations can lead to low levels of student involvement. Students’ engagement and satisfaction are good indicators of the quality and effectiveness of online programs.